Picking the winner? Empirical evidence on the targeting of R&D subsidies to start-ups - Uwe Cantner; Sarah Kösters (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
This paper investigates the allocation of R&D subsidies given to start-ups. Considering the coexistence of various R&D project schemes, we take an aggregate view and analyze the determinants of the receipt of (any) R&D subsidies within the first three business years of the start-ups. We argue that policymakers and funding authorities follow a strategy of picking the winner. Analyzing a unique data set of start-ups in the East German state of Thuringia, we conduct logistic regressions and find ambiguous support. R&D subsidies are given to start-ups with innovative business ideas, especially academic spin-offs. On the other hand, the ambitions and the patent stock of the founder(s) do not decide the receipt of R&D subsidies. These insights into the overall allocation of R&D subsidies are important since they have implications for policy effectiveness and efficiency. The implied difficulties of policy targeting fundamentally question the massive subsidization of private R&D.
Keywords: O38; L26; L52; 330; Start-ups; R&D subsidies; Subsidy allocation; Forschungssubvention; Unternehmensgründung; Wirtschaftsförderung; Forschungskooperation; Wirkungsanalyse; Thüringen